PENERAPAN PENDEKATAN KONSTRUKTIVISME MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) DALAM KEGIATAN LESSON STUDY UNTUK MENINGKATKAN KUALITAS PROSES DAN HASIL BELAJAR STRATEGI BELAJAR MENGAJAR - Utami, Budi; Sugiharto, Sugiharto; Indriyanti, Nurma Yunita; Martini, Kus Sri (Jurnal Inovasi Pendidikan, 2011)
Teaching and Learning Strategies course is a compulsory subject in the course Chemical Education Department of Mathematics and Science Education Guidance and Counseling UNS with weights 2 credits. As a high school chemistry teacher candidates take courses relefan stock and standard and suit the needs of stakeholders, should have a pedagogical competence, personal competence, social competence, and professional competence (Act No. 14 th 2005 chapter IV of chapter 8-10) . This research aims to improve the quality of the learning process in the course of Teaching and Learning Strategies using the constructivist approach through learning model Think-Pair-Share (TPS) in the activities of Lesson Study. The study included a descriptive study. Data collection was carried out with observations on the activities of lesson study and observation results are set forth in the form of descriptive. The experiment was conducted on students participating in the course of Teaching and Learning Strategies odd semester 2010/2011 academic year in the course Chemical Education Guidance and Counseling University PMIPA Eleven Maret Surakarta (UNS). Activities conducted open lessons three times, with three times three times the Plan and Do (Open Lesson). Each lesson conducted open-end reflection. The result of the implementation of lesson study on the subject of Teaching and Learning Strategies by applying the constructivist approach through learning model Think-Pair-Share (TPS) concluded that the application of constructivist approach through learning model Think-Pair-Share (TPS) in Lesson Study activities to improve the quality of the learning process on Teaching and Learning Strategies course, this can be seen that the achievement of the final cycle is obtained: indicators of student achievement in working on student worksheet is 100%, the results of assessment of students' task of preparing the paper with a value greater / equal to B is 100%, liveliness student increase is 17.6% completed the first indicator, second indicator 32.4% complete and 100% complete the seven indicators, student affective value increase that value is greater/equal to B is 100% (no value C). Application of cons-tructivist approach through learning model Think-Pair-Share (TPS) in Lesson Study activities to improve learning outcomes of Teaching and Learning Strategies that students who obtain a value greater/equal to 70 (B) otherwise complete as much as 76.4%. Based on responses to questionnaires filled out by students learning at the end of learning, shows that the learning model used by researchers, received a positive response, so that students want lecturers to implement active learning in the classroom.